Sharing the Expertise: Middle School Girls and Community Members as Solution and Communication Partners (LEARNing Landscapes, 2016)
The documentary lm Hicklin Lake: A Hopeful Future shows how middle school girls took on the roles of expert solution designers and communicators while partnering with multiple community members in an afterschool science club. Working towards justice for the future of a local toxic lake, the community members and girls co-investigated the complex story behind the lake’s toxicity and needed actions to clean it up for future generations. This lm is one product of a mutually bene cial experience between middle school girls and the community, where all learned about an unnatural problem that has natural solutions.
Keywords: community; education; science; solution design; girl; communication; environment